(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Contemporary researches show that triggering interest can enhance students’ thinking skills, creativity, joy of learning and improved performance. The digital technologies can be beneficial for students’ learning engagement and motivation. The digital context helps students to keep positivity in education process that allows to activate attention, memory, and makes learning skills better. Augmented Reality is one of technologies that lets you interact with the real world and virtual objects at the same time. Augmented Reality application enables faster comprehension of complex spatial problems and relationships, which makes it useful during the learning process of engineering graphic courses. In this paper the application of AR technologies in RTU engineering courses is described. The results of this approach will be useful for vocational school teachers, college and university teachers in the successful integration of AR technologies in the teaching process.